Comparison of methotrexate and methylprednisolone as addition to antifibrotic therapy in progressive pulmonary fibrosis due to COVID-19 - Kerget, Buğra; Gülbahar, Burcu Nur; Çınar, İsmail; Alper, Fatih; Sağlam, Leyla (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background: Post-covid pulmonary fibrosis (PCPF) is an essential cause of hypoxic respiratory failure, especially in patients with severe COVID-19 infection. In our study, we aimed to compare the effectiveness of methylprednisolone and methotrexate treatments in patients diagnosed with PCPF and in whom progression was observed despite nintedanib treatment. Methods: Forty-eight patients diagnosed with PCPF between April 2022 and February 2023 were followed up in our study. Progressive pulmonary fibrosis was observed in 18 of these patients despite nintedanib treatment. Nintedanib + methylprednisolone treatment was started in Group 1 patients, and nintedanib + methotrexate treatment was started in Group 2 patients, and after three months, a respiratory function test (PFT), 6-minute walk test (6MWT), saturation, pulse, and side effect levels were compared.Results: In comparing the groups at the end of the 3rd month, the change in PFT parameters was higher in Group 2 patients than in Group 1 patients. However, there was no statistically significant difference. However, the increase in fingertip saturation, 6MWT levels, and decrease in pulse levels were statistically significantly different in Group 2 patients compared to Group 1 patients (p=0.001 for all).  It was observed that complaints of muscle and joint pain, weight gain, and atrophy in peripheral extremities in Group 1 patients were statistically significantly higher than in Group 2 patients (p=0.001, 0.002, 0.001, respectively).Conclusion: Methotrexate can be used as an alternative to methylprednisolone in PCPF due to its low side effect profile and its effectiveness in PFT, 6MWT, and saturation levels.